PRACTICAL STRATEGIES FOR INTEGRATING MOBILE APPS INTO ENGLISH LANGUAGE TEACHING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The integration of mobile applications into English language teaching has transformed traditional pedagogical practices. Mobile-Assisted Language Learning (MALL) provides flexible, individualized learning opportunities that support both inclass and out-of-class language development. This article explores evidence-based strategies for incorporating mobile apps into English teaching, focusing on the flipped classroom approach, gamification, skill-based mobile learning, and digital assessment. The discussion highlights practical classroom implications and emphasizes the importance of meaningful, pedagogy-driven technology use to enhance learning outcomes.